Mesoporous self-assembled nanoparticles of biotransesterified cyclodextrins and nonlamellar lipids as carriers of water-insoluble substances. Issue 36 (30th August 2016) - Zerkoune, Leïla; Lesieur, Sylviane; Putaux, Jean-Luc; Choisnard, Luc; Gèze, Annabelle; Wouessidjewe, Denis; Angelov, Borislav; Vebert-Nardin, Corinne; Doutch, James; Angelova, Angelina
Abstract : Biotransesterified cyclodextrin βCD- n C10 induces Im 3 m cubic lattice nanostructures in host Pn 3 m monoglyceride lipid assemblies as evidenced by SAXS and cryo-TEM (FFT) analyses. Abstract : Soft mesoporous hierarchically structured particles were created by the self-assembly of an amphiphilic deep cavitand cyclodextrin βCD- n C10 (degree of substitution n = 7.3), with a nanocavity grafted by multiple alkyl (C10 ) chains on the secondary face of the βCD macrocycle through enzymatic biotransesterification, and the nonlamellar lipid monoolein (MO). The effect of the non-ionic dispersing agent polysorbate 80 (P80) on the liquid crystalline organization of the nanocarriers and their stability was studied in the context of vesicle-to-cubosome transition. The coexistence of small vesicular and nanosponge membrane objects with bigger nanoparticles with inner multicompartment cubic lattice structures was established as a typical feature of the employed dispersion process. The cryogenic transmission electron microscopy (cryo-TEM) images and small-angle X-ray scattering (SAXS) structural analyses revealed the dependence of the internal organization of the self-assembled nanoparticles on the presence of embedded βCD- n C10 deep cavitands in the lipid bilayers. The obtained results indicated that the incorporated amphiphilic βCD- n C10 building blocks stabilize the cubic lattice packing in the lipid membrane particles, which displayed structural features beyond the traditional CD nanosponges. UV-Vis spectroscopy was employed to characterize the nanoencapsulation of a model hydrophobic dimethylphenylazo-naphthol guest compound (Oil red) in the created nanocarriers. In perspective, these dual porosity carriers should be suitable for co-encapsulation and sustained delivery of peptide, protein or siRNA biopharmaceuticals together with small molecular weight drug compounds or imaging agents.